2009
DOI: 10.1117/12.820446
|View full text |Cite
|
Sign up to set email alerts
|

Active x-ray optics for the next generation of x-ray telescopes

Abstract: The immediate future for X-ray astronomy is the need for high sensitivity, requiring large apertures and collecting areas, the newly combined NASA, ESA and JAXA mission IXO (International X-ray Observatory) is specifically designed to meet this need. However, looking beyond the next decade, there have been calls for an X-ray space telescope that can not only achieve this high sensitivity, but could also boast an angular resolution of 0.1 arc-seconds, a factor of five improvement on the Chandra X-ray Observator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…This caused a glue layer with a variable thickness and some print-through, due to stress, was evident on the optical surface. This was seen in scans taken of a second prototype with piezoelectric devices attached, using the LTP as described in Atkins et al 9 and shown in figure 4. The theoretical form of the optic is shown with scans of the mirror with the power supply switched on and 0V applied, the power supply switched off and with the difference between the two.…”
Section: Piezoelectric Actuatorsmentioning
confidence: 97%
See 2 more Smart Citations
“…This caused a glue layer with a variable thickness and some print-through, due to stress, was evident on the optical surface. This was seen in scans taken of a second prototype with piezoelectric devices attached, using the LTP as described in Atkins et al 9 and shown in figure 4. The theoretical form of the optic is shown with scans of the mirror with the power supply switched on and 0V applied, the power supply switched off and with the difference between the two.…”
Section: Piezoelectric Actuatorsmentioning
confidence: 97%
“…The mirror was electroformed at UCL in an in-house facility. 9 Thirty curved piezoelectric actuators designed and manufactured at the University of Birmingham (UoB), were attached to the back of the mirror to allow active manipulation of the surface. The manufacture processes of the mirror are described in Atkins et al 9 are shown in figure 2, where the top graph shows the scanned data with the theoretical form the optic should have had.…”
Section: Prototype Design and Manufacturementioning
confidence: 99%
See 1 more Smart Citation
“…The already realized prototype has a dimension of 100 mm x 300 mm x < 1 mm. It is realized with a shell made of Nickel and 30 piezoelectric actuators, 200 μm thick, bonded to the back of this shell [7]. Electroformed Ni plates were considered for easiness of procurement.…”
Section: Deposition Of Piezoelectric Devices On the Thin Substrates Tmentioning
confidence: 99%
“…A technology development programme entitled Smart X-ray Optics (SXO) has been just successfully completed in the UK, funded by the EPSRC to start development of such optics. The major output from this program, relevant to X-ray telescope optics, is a prototype, single reflection grazing incidence reflector, 100x300x0.4 mm Nickel shell, with 30 piezoelectric actuators of thickness order 200 microns bonded to the back 7 . This will demonstrate the principle and manufacturing techniques required to produce an actively adjustable X-ray mirror shell.…”
Section: Introductionmentioning
confidence: 99%